Art Expertise and the Processing of Titled Abstract Art. (April 2018) - Mullennix, John W.; Robinet, Julien
The effect of art expertise on viewers' processing of titled visual artwork was examined. The study extended the research of Leder, Carbon, and Ripsas by explicitly selecting art novices and art experts. The study was designed to test assumptions about how expertise modulates context in the form of titles for artworks. Viewers rated a set of abstract paintings for liking and understanding. The type of title accompanying the artwork (descriptive or elaborative) was manipulated. Viewers were allotted as much time as they wished to view each artwork. For judgments of liking, novices and experts both liked artworks with elaborative titles better, with overall rated liking similar for both groups. For judgments of understanding, type of title had no effect on ratings for both novices and experts. However, experts' rated understanding was higher than novices, with experts making their decisions faster than novices. An analysis of viewers' art expertise revealed that expertise was correlated with understanding, but not liking. Overall, the results suggest that both novices and experts integrate title with visual image in similar manner. However, expertise differentially affected liking and understanding. The results differ from those obtained by Leder et al. The differences between studies are discussed.